Effects of renewable and non‐renewable energy consumption on CO2 emissions in India: Empirical evidence from disaggregated data analysis. Issue 1 (23rd August 2020) - Sahoo, Malayaranjan; Sahoo, Jayantee
Abstract : In this paper, we examined the relationship between renewable and non‐renewable energy consumption on CO2 emissions in India by taking disaggregated data from 1965 to 2018. In order to determine the effect of long‐run elasticity of independent variables on dependent variables, we have used ARDL bound testing approach. The directions of causality of the variables are investigated by Toda–Yamamoto Granger causality test. The long‐run results reveal that hydro energy consumption has a positive impact on CO2 emissions but not significant. However, nuclear energy consumption indicates that there is a negative effect on CO2 emissions. It reveals that all non‐renewable energy consumption sources have positive and significant effect on CO2 emissions.